Ekologiczna realizacja miasta "solarCity" inwestycją w przyszłość zrównoważonego rozwoju obszarów miejskich w Austrii = Ecological implementation city of the "solarCity" investment in the future of sustainable urban development in Austria - Wojtyszyn, Bogusław J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A good practice in solving climate issues both locally and globally is develop sustainable solar buildings of urban areas in Austria. City Linz realized in the district Pichling project of ecological settlements "solarCity" developed by an international team of recognized architects and professionals from low-energy building systems.
Keywords: zrównoważone budownictwo solarne; wskaźniki ekologiczne; zrównoważone obszary miejskie; ekologia miasta; sustainable buildings solar; ecological indicators; sustainable urban development; urban ecology